PENGARUH KUALITAS PELAYANAN, FASILITAS DAN CITRA TERHADAP KEPUASAN MASYARAKAT PADA PELAYANAN PUSKESMAS MULIA BARU KABUPATEN KETAPANG PROVINSI KALIMANTAN BARAT - Diana Sari Wijayanti, Irine; Prihartanto Eko Wibowo; Khoiri Najib; Purwanta; Fanny (LPPM Akademi Manajemen Administrasi Yogyakarta, 2024)
The aim of this research is to determine the influence of service quality, facilities and image partially or simultaneously on community satisfaction with the services of the Mulia Baru District Health Center. Ketapang, West Kalimantan. This type of quantitative research with a total sample of 92 samples. The types of data used are primary data and secondary data, which were obtained from distributing questionnaires and literature studies. Data testing in this research is validity test, reliability test, classic assumption test consisting of normality, multicollinearity and heteroscedasticity tests, then multiple linear analysis tests, t test (partial), F test (simultaneous), correlation test and determination test. processed using SPSS version 20.0 for Windows computer software. The results of the research show that partially the facility and image variables have an influence on community satisfaction, while the service quality variable has no influence on community satisfaction with the services of the Mulia Baru District Health Center. Ketapang, West Kalimantan. And simultaneously it is significant for community satisfaction with Mulia Baru Community Health Center services and is very strongly correlated. Apart from that, the variables of service quality, facilities and image contribute 70.5% to community satisfaction, while the remaining 29.5% is influenced by other variables not examined in this research.